Evaluation of risk factors for postoperative neurologic intensive care admission after brain tumor craniotomy: A single-center longitudinal study - Konish Biswas; Sanjay Agrawal; Priyanka Gupta; Rajnish Arora (Journal of Anaesthesiology Clinical Pharmacology)
Background and Aims: Perioperative variable parameters can be significant risk factors for postoperative intensive care unit (ICU) admission after elective craniotomy for intracranial neoplasm, as assessed by various scoring systems such as Cranio Score. This observational study evaluates the relationship between these factors and early postoperative neurological complications necessitating ICU admission. Material and Methods: In total, 119 patients, aged 18 years and above, of either sex, American Society of Anesthesiologists (ASA) grades I–III, scheduled for elective craniotomy and tumor excision were included. The primary objective was to evaluate the relationship between perioperative risk factors and the incidence of early postoperative complications as a means of validation of the Cranio Score. The secondary outcomes studied were 30-day postoperative morbidity/mortality and the association with patient-related risk factors. Results: Forty-five of 119 patients (37.82%) required postoperative ICU care with the mean duration of ICU stay being 1.92 ± 4.91 days. Tumor location (frontal/infratemporal region), preoperative deglutition disorder, Glasgow Coma Scale (GCS) less than 15, motor deficit, cerebellar deficit, midline shift >3 mm, mass effect, tumor size, use of blood products, lateral position, inotropic support, elevated systolic/mean arterial pressures, and duration of anesthesia/surgery were associated with a higher incidence of ICU care. Maximum (P = 0.035, AOR = 1.130) and minimum systolic arterial pressures (P = 0.022, Adjusted Odds Ratio (AOR) = 0.861) were the only independent risk factors. Cranio Score was found to be an accurate predictor of complications at a cut-off point of >10.52%. The preoperative motor deficit was the only independent risk factor associated with 30-day morbidity (AOR = 4.66). Conclusion: Perioperative hemodynamic effects are an independent predictor of postoperative ICU requirement. Further Cranio Score is shown to be a good scoring system for postoperative complications.